The Influence of Customer Satisfaction on Grab Services in Malaysia - Adam, Muhammad; Kee, Daisy Mui Hung; Junaina, Intan; Fadhilah, Nur; Uwais, Nurul; Al Rashidi, Fatimah; Al Shammari, Hadeel; Quttainah, Majdi Anwar; Srivastava, Aditi; Pandey, Rudresh (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
The purpose of this paper is to examine and identify the factors that influence Grab users’ satisfaction. It is undeniable that customer’s satisfaction is really important in every business especially in services industry. This research is conducted in a specific group of respondents. The respondents consist of staff and students of USM. The methodology that was used is the quantitative questionnaire type of form. This study was expected to give a bright side or any recommendations and improvements to the Grab Holdings Incorporation, especially in enhancing their customers’ satisfaction. Based on the findings, this study could provide recommendations for practices and future research.